Clinical characteristics and outcomes after new‐onset seizure among Zambian children with HIV during the antiretroviral therapy era. Issue 2 (1st April 2022) - Ravishankar, Mathura; Dallah, Ifunanya; Mathews, Manoj; Bositis, Christopher M.; Mwenechanya, Musaku; Kalungwana‐Mambwe, Lisa; Bearden, David; Navis, Allison; Elafros, Melissa A.; Gelbard, Harris; Theodore, William H.; Koralnik, Igor J.; et al.
Abstract: Objective: This study describes clinical profiles including human immunodeficiency virus (HIV) disease history and seizure etiology among children living with HIV presenting with new‐onset seizure during the era of antiretroviral therapy (ART) in Zambia. 30‐day mortality and cause of death are also reported. Methods: Children living with HIV (CLWHIV) with new‐onset seizures were prospectively evaluated at one large urban teaching hospital and two non‐urban healthcare facilities. Interviews with family members, review of medical records, and where needed, verbal autopsies were undertaken. Two clinicians who were not responsible for the patients' care independently reviewed all records and assigned seizure etiology and cause of death with adjudication as needed. Results: From April 2016 to June 2019, 73 children (49 urban, 24 rural) were identified. Median age was 6 years (IQR 2.2‐10.0) and 39 (53%) were male children. Seizures were focal in 36 (49%) and were often severe, with 37% presenting with multiple recurrent seizures in the 24 hours before admission or in status epilepticus. Although 36 (49%) were on ART at enrollment, only 7 of 36 (19%) were virally suppressed. Seizure etiologies were infectious in over half (54%), with HIV encephalitis, bacterial meningitis, and tuberculous meningitis being the most common. Metabolic causes (19%) included renal failure and hypoglycemia. Structural lesions identified on imaging accounted for 10% of etiologies and included stroke and non‐accidental trauma. No etiology could be identified in 12 (16%) children, most of whom died before the completion of clinical investigations. Twenty‐two (30%) children died within 30 days of the index seizure. Significance: Despite widespread ART roll out in Zambia, new‐onset seizure in CLWHIV occurs in the setting of advanced, active HIV disease. Seizure severity/burden is high as is early mortality. Enhanced programs to assure early ART initiation, improve adherence, and address ART failure are needed to reduce the burden of neurological injury and premature death in CLWHIV.